Policies for agroindustrial development in Latin America and the Caribbean - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
The articles included in this collection serve two purposes. First, they contribute to the ideas and proposals for action in this field which became part of the Plan of Joint Action for Agricultural Reactivation in Latin America and the Caribbean (PLANALC), the coordination of which was entrusted to IICA by the Ninth Inter-American Conference of Ministers of Agriculture (Ottawa, Canada 1987). Secondly, it has permitted the compilation of original articles in a field in which technical literature is very scarce and widely dispersed. The objectives of the seminar were: a) to analyze the conditions which have led to the current state of development of agroindustry in LAC and to evaluate how these conditions can contribute, and are contributing, to agricultural modernization, economic stabilization and structural change; b) to asess the opportunities and challenges for the development of competitive agroindustrial systems; c) to analyze the options available as to trade policies and others related to the abovementioned objectives, and to evaluate the role the State, the private sector and financial institutions can play in the design and implementation of such policies; and d) to draw up specific guidelines and recommendations concerning international cooperation, with a view to strenghthening the region's capacity to reactivate its agriculture and accelerate the rate of growth and recovery of its economy, though agroindustrial development. Appendix I presents the complete agenda of the seminar, appendix II is a summary of the closing session, and appendix III contains the list of participants.